The limits of historiography : genre and narrative in ancient historical texts - Kraus, Christina Shuttleworth, 1958- (Mnemosyne, Supplements, 1999)
This volume explores the intersection between historiography and related genres in antiquity. Papers cover the geographical range from China through the near east to the classical period in the Mediterranean. Topics addressed include the place in ancient Chinese historiography of philosophical argument; the nature and kind of historical text in the Hittite, Babylonian, Persian and biblical periods, including (for the first time) a full transliteration and translation of the Old Hittite story of Anum-hirbi and Zalpa, and a new interpretation of the Darius inscription at Behistun; and the relation of rhetorical stratagems and theory to Sallust, Livy, and Tacitus. Contributors also consider the relationship between texts, including the war narratives of Herodotus and Thucydides, and the propriety of different schemes of generic classification.